Outflowing disk formation in B supergiants due to rotation and bi-stability in radiation driven winds - Curé, M. (2005)
The effects of rapid rotation and bi-stability upon the density contrast between the equatorial and polar directions of a B[e] supergiant are re-investigated. Based on a new slow solution for different high rotational radiation-driven winds and the fact that bi-stability allows a change in the line-force parameters (α, k, and δ), the equatorial densities are about 102-104 times higher than the polar ones. These values are in qualitative agreement with the observations.